A New Android Application Framework (AAF) For API PM2.5 Data Management System - TAN, TAN CHIU SI; Hashim, Nor Haslina; Sadun, Amirul Syafiq (Progress in Engineering Application and Technology, 2021)
Air Pollution Index (API) is used in Malaysia to measure the ambient air quality and PM2.5 is one of its parameters. Therefore, it is important to monitor the PM2.5 for ambient air quality monitoring and especially during haze event. However, most of the PM2.5 sampler available for research and monitoring by university and monitoring provider are in manual mode in which the data was logged into the equipment data logger and it was manually extracted from the data logger to personal computer to analyze. This would cause a difficulties of monitoring person to monitor and report the data in a real time. The problem become worst during the Movement Control Order (MCO) period as well as during the haze event or rainy season as the access to the site for data extraction was limited. Therefore, this project is aimed to propose an Android Application Framework (AAF) containing IoT device to monitor the real-time ambient air quality and disseminate computed API information through social media platform. Mobile apps such as Blynk apps was encouraged as it is simple and user friendly to monitor real-time ambient PM2.5. Mobile apps with high mobility enable user to control remotely on desirable outcomes at any time. There are six stages to plan and accomplish in relation to make proposed AAF succeed. This included the E-Sampler interface with IoT, mobile application, data management, data management system, API judgement, and information dissemination. As a result, proposed AAF has fully utilized in obtaining API in monitoring area. IoT device has successfully interface with E-Sampler, to obtain raw data and able to be downloaded for further analysis. In conclusion, AAF has functioned great, enabling the collection of raw data at fingertips. The API information were collected, calculated, analyzed, and finally disseminate to the public through Facebook and Instagram.